Antithrombotic management in patients with percutaneous coronary intervention requiring oral anticoagulation - Zalewski, Jarosław; Undas, Anetta (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
The dynamic evolution of therapeutic options including the use of vitamin K antagonists (VKA), non-vitamin K oral anticoagulants (NOAC), more potent antiplatelet drugs as well as new generation drug-eluting stents could lead to the view that the current recommendations on the management of patients with percutaneous coronary intervention (PCI) requiring oral anticoagulation do not keep up with the results of several clinical studies published within the last 5 years. In the present overview, we summarize the recent advances in antithrombotic management used in atrial fibrillation patients undergoing PCI for stable coronary artery disease or acute coronary syndrome (ACS). The safety and efficacy of prasugrel and ticagrelor taken with oral anticoagulants also remain to be established in randomized trials; therefore the P2Y12 inhibitor clopidogrel on top of aspirin or without is now recommended to be used together with a VKA or NOAC. It is still unclear which dose of a NOAC in combination with antiplatelet agents and different stents should be used in this clinical setting and whether indeed NOAC are safer compared with VKA in such cardiovascular patients. Moreover, we discuss the use of anticoagulation in addition to antiplatelet therapy for secondary prevention in patients with ACS. To minimize bleeding risk in anticoagulated patients following PCI or ACS, the right agent should be prescribed to the right patient at the right dose and supported by regular clinical evaluation and laboratory testing, especially assessment of renal function when a NOAC is used.